Manufacturing method for r-t-b based sintered magnet
A multi-stage heat treatment process for RTB sintered magnets controls grain boundaries and diffuses elements to enhance coercive force and residual magnetic flux density, addressing thermal demagnetization and heavy rare earth element scarcity.
Patent Information
- Application Number
- JP2024141908
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-29
- Filing Date
- 2024-08-23
- Publication Date
- 2025-04-10
AI Technical Summary
RTB sintered magnets face issues with irreversible thermal demagnetization due to low coercive force, and the use of heavy rare earth elements like Dy, which are scarce and volatile in supply, complicates the production of high-performance magnets.
A multi-stage heat treatment process is applied to RTB sintered magnets, adjusting conditions to control the grain boundary phase and diffuse elements like Cu or Ga, maintaining high residual magnetic flux density while suppressing a decline in coercive force.
The method produces RTB sintered magnets with enhanced coercive force and residual magnetic flux density, overcoming the limitations of heavy rare earth element reliance and ensuring stable magnetic properties.
Smart Images

Figure 2025060420000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an RTB based sintered magnet. [Background technology]
[0002] RTB sintered magnets (R is a rare earth element containing at least one selected from the group consisting of Nd, Pr and Ce, T is an element containing at least one selected from the group consisting of Fe, Co, Al, Mn and Si, and the mass ratio of T is 90% or more Fe, and B is boron) are known as the most high-performance permanent magnets, and are used in a variety of motors, such as motors for electric vehicles (EV, HV, PHV, etc.), motors for industrial equipment, and home appliances. RTB sintered magnets are mainly R2T 14 It is composed of a main phase made of B compounds and a grain boundary phase (hereinafter sometimes simply referred to as "grain boundary") located at the grain boundary portion of this main phase. 14 The B compound is a ferromagnetic phase with high magnetization.
[0003] RTB sintered magnets have a coercive force H cJ (Hereinafter, simply "coercive force" or "H cJ This causes a problem of irreversible thermal demagnetization, as the magnetization temperature drops and the magnetization rate drops. For this reason, RTB sintered magnets, which are used in electric vehicle motors in particular, have a high H cJ It is required that the applicant have:
[0004] In RTB sintered magnets, R2T 14 When a part of the light rare earth elements (mainly Nd and / or Pr) contained in R in the B compound is replaced with heavy rare earth elements (mainly Dy and / or Tb), H cJ It is known that the H cJ will improve.
[0005] However, R2T 14 When the light rare earth elements in the B compound are replaced with heavy rare earth elements, the H of the RTB sintered magnetcJ While the residual magnetic flux density B r (Hereinafter, simply "B r In addition, heavy rare earth elements, especially Dy, are scarce and have limited production areas, so their supply is unstable and their prices fluctuate greatly. For this reason, in recent years, users have been promoting the use of H as little as possible without using heavy rare earth elements. cJ There is a need to improve this.
[0006] Patent Document 1 discloses an RTB rare earth sintered magnet with increased coercivity while reducing the Dy content. The composition of this sintered magnet is limited to a specific range in which the amount of B (boron composition ratio or boron concentration) is relatively low compared to commonly used RTB alloys, and contains one or more metallic elements selected from Al, Ga, and Cu. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2013 / 008756 Summary of the Invention [Problem to be solved by the invention]
[0008] As described in Patent Document 1, the content of heavy rare earth elements is reduced while maintaining high B r and high H cJ In order to realize an RTB-based sintered magnet with this property, technology is being investigated that diffuses elements contained in the diffusion source from the surface of the magnet to its interior, and technology that controls the thickness of the two-particle grain boundary by relatively reducing the amount of B (grain boundary modification technology).
[0009] According to the study by the present inventors, it was found that the modification of the grain boundary depends on the conditions of the heat treatment of the RTB sintered magnet. In addition, when the diffused RTB sintered magnet contains a specific metal element (e.g., Cu or Ga), the B r It was found that there is a possibility of a decrease.
[0010] The method for producing an RTB based sintered magnet disclosed herein is characterized in that the heat treatment conditions are adjusted to produce a B r While suppressing the decline of cJ This makes it possible to realize an RTB-based sintered magnet having the above properties. [Means for solving the problem]
[0011] In an exemplary embodiment, a method for producing an RTB based sintered magnet according to the present disclosure includes the steps of: preparing an RTB based sintered magnet material (R is a rare earth element and must include at least one selected from the group consisting of Nd, Pr, and Ce; T is at least one selected from the group consisting of Fe, Co, Al, Mn, and Si; 90% or more of T is Fe in terms of mass ratio; and B is boron); and preparing an RA alloy (R is at least one rare earth element and must include at least one selected from the group consisting of Nd, Pr, and Ce; A is Fe, Co, Ni, Al, Ag, Zn, Si, Sn, the element being at least one selected from the group consisting of Ga, B, and C; a first heat treatment step of heat treating the RTB based sintered magnet material at a first temperature of 400°C to 430°C for 30 to 300 minutes; a second heat treatment step of heat treating the RTB based sintered magnet material at a second temperature of 430°C to 530°C for 30 to 200 minutes after the first heat treatment step; and a third heat treatment step of heat treating the RTB based sintered magnet material at a second temperature of 430°C to 530°C for 30 to 200 minutes. The second temperature is 30°C to 130°C higher than the first temperature. Effect of the Invention
[0012] The method for producing an RTB based sintered magnet disclosed herein is characterized in that the heat treatment conditions are adjusted to produce a B r While suppressing the decline of cJ It is therefore possible to realize an RTB sintered magnet having the above properties. [Brief description of the drawings]
[0013] [Figure 1A] FIG. 2 is a schematic diagram showing the main phase and grain boundary phase of an RTB based sintered magnet. [Figure 1B] FIG. 1B is a further enlarged schematic diagram of the dashed rectangular area in FIG. 1A. [Diagram 2] 1 is a flowchart outlining a method for producing an RTB based sintered magnet according to an embodiment of the present disclosure. [Diagram 3] 3A to 3C are diagrams illustrating an example of a heat treatment process in the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, an embodiment of the present disclosure will be described with respect to an RTB based sintered magnet.
[0015] Conventionally, in an RTB sintered magnet, for example, when (1) the content of R (R is a rare earth element including at least one selected from the group consisting of Nd, Pr, and Ce) is set to 27 mass% or more and 34 mass% or less of the entire RTB sintered magnet, (2) T is an element including at least one selected from the group consisting of Fe, Co, Al, Mn, and Si, and the mass ratio of T is 90% or more of Fe, and (3) the molar ratio of T to B ([T] / [B]) is more than 14.0 and 15.0 or less, an element such as Ga is added to thicken the two-particle grain boundary and increase the H content. cJ It is known that it is possible to improve
[0016] The molar ratio of T to B ([T] / [B]) is the ratio (a / b) of the number of moles (a) obtained by dividing the analytical value (mass%) of the concentration of each element (Fe and at least one of Co, Al, Mn, and Si) constituting T by the atomic weight of each element, to the number of moles (b) obtained by dividing the analytical value (mass%) of the concentration of B by the atomic weight of B.
[0017] When the molar ratio of T to B ([T] / [B]) exceeds 14.0, the B content is R2T 14 This means that the ratio of the main phase (R2T 14 The amount of B is reduced relative to the amount of T used to form the compound (B).
[0018] Next, the basic structure of an RTB based sintered magnet will be described.
[0019] RTB sintered magnets have a structure in which powder particles of raw alloys are bonded together by sintering, and are mainly 14 It is composed of a main phase made of B compounds and a grain boundary phase located at the grain boundaries of this main phase.
[0020] FIG. 1A is a schematic diagram showing the main phase and grain boundary phase of an RTB based sintered magnet, and FIG. 1B is a schematic diagram further enlarging the dashed rectangular area in FIG. 1A. In FIG. 1A, an arrow of 5 μm in length is shown as an example for reference, showing the reference length of the size. As shown in FIG. 1A and FIG. 1B, an RTB based sintered magnet is mainly composed of R2T 14 The grain boundary phase 14 is composed of a main phase 12 made of a B compound and a grain boundary phase 14 located at the grain boundary portion of the main phase 12. As shown in FIG. 1B, the grain boundary phase 14 is composed of two R2T 14 B compound grains are adjacent to each other in the two-particle grain boundary phase 14a, and there are three or more R2T 14 The B compound grains include adjacent grain boundary triple junctions 14b.
[0021] R2T, which is main phase 12 14The B compound is a ferromagnetic phase with high saturation magnetization and anisotropic magnetic field. Therefore, in RTB sintered magnets, the R2T 14 By increasing the proportion of B compounds, r It can improve R2T 14 In order to increase the ratio of B compounds, the amounts of R, T, and B in the raw alloy should be adjusted to R2T 14 The stoichiometric ratio of the B compound (R amount:T amount:B amount = 2:14:1) should be as close as possible. 14 When the amount of B or R for forming the B compound is less than the stoichiometric ratio, the grain boundary phase 14 generally contains an Fe phase or an R2T phase. 17 Soft magnetic phases such as H cJ However, the amount of B is reduced by R2T 14 When the amount of the B compound is less than the stoichiometric ratio and at least one selected from the group consisting of Cu, Ga, Ni, Ag, Zn, and Sn is contained, R2T 17 The grain boundaries are thickened by the formation of transition metal-rich phases (e.g., RT-Ga phases) at the grain boundaries from the phase, resulting in high H cJ can be obtained.
[0022] In RTB sintered magnets, it is important to control the two-particle grain boundary by optimizing the heat treatment conditions for the RTB sintered magnet. The inventors' research has revealed that the two-particle grain boundary can be appropriately controlled and excellent magnetic properties can be achieved by adjusting the conditions (particularly the temperature) of the two-stage heat treatment, which is performed with a cooling step in between, within an appropriate range.
[0023] <Embodiment> Next, an outline of the method for producing an RTB based sintered magnet of this embodiment will be described with reference to Fig. 2. As shown in Fig. 2, the method for producing an RTB based sintered magnet of this embodiment includes a step (S1) of preparing an RTB based sintered magnet material, a step (S2) of preparing a diffusion source of an RA alloy, and a step (S3) of diffusing elements contained in the diffusion source from the diffusion source into the RTB based sintered magnet material.
[0024] Furthermore, as shown in FIG. 2, the method for manufacturing the R-T-B sintered magnet in the present embodiment includes a first heat treatment step (S10) of heat-treating the R-T-B sintered magnet material at a first temperature (T1) of 400°C or higher and 430°C or lower for 30 minutes or longer and 300 minutes or shorter, a step (S20) of cooling the temperature of the R-T-B sintered magnet material to a temperature of 300°C or lower, and a second heat treatment step (S30) of heat-treating the R-T-B sintered magnet material at a second temperature (T2) of 430°C or higher and 530°C or lower for 30 minutes or longer and 200 minutes or shorter. Here, the second temperature is 30°C or higher and 130°C or lower higher than the first temperature.
[0025] Also, the composition of the R-T-B sintered magnet material is R: 26.5 to 30.5 mass%, B: 0.85 to 0.95 mass%, and T: 61.5 mass% or more
[0026] Furthermore, it contains at least one selected from the group consisting of Cu, Ga, Ni, Ag, Zn, and Sn, and the molar ratio [T] / [B] of T to B is more than 14.0.
[0027] Hereinafter, each of the above steps will be described.
[0028] <Step of forming R-T-B alloy powder (S1)> In the present embodiment, as a step of pulverizing the raw material alloy to obtain a powder of the R-T-B alloy (fine pulverization step), a step S10 of forming the R-T-B alloy powder by a jet mill pulverization device is performed. Before step S10, it is preferable to perform a hydrogen pulverization step to produce a coarse pulverized powder of the R-T-B alloy. Here, the composition of the R-T-B alloy is as follows. R: 26.3 to 30.3 mass% (R is a rare earth element and necessarily contains at least one of Nd and Pr), B: 0.85 to 0.95 mass%, T: 61.5 mass% or more
[0029] Furthermore, it contains at least one selected from the group consisting of Cu, Ga, Ni, Ag, Zn, and Sn, and the molar ratio of T to B, [T] / [B], is greater than 14.0.
[0030] It is preferable that the following conditions are also satisfied. Tb: 0.30 mass% or less, and Dy: 0.30 mass% or less
[0031] By adjusting the amount of B to the above range, R6T is formed at the grain boundaries of RTB-based sintered magnets. 13 Ga is formed and the two-grain boundary becomes thicker, for example, B of 1.39T or more. r and high H exceeding 1640kA / m cJ In order to reliably thicken the two-particle grain boundary, it is more preferable that the molar ratio of T ([T] / [B]) is more than 14.0 and 15.0 or less.
[0032] The RTB alloy having the above composition can be produced by, for example, a strip casting method. The RTB alloy may contain a plurality of alloy components having different compositions. By having the above composition as a whole, the above-mentioned two-particle grain boundary is thickened, and a high H cJ It is possible to obtain the effect of realizing the above.
[0033] The hydrogen pulverization process may include a hydrogen absorption process in which hydrogen is absorbed into the RTB alloy at a temperature of 200°C or less in a treatment chamber, and a dehydrogenation process in which hydrogen is exhausted from inside the treatment chamber and the RTB alloy is heated to a temperature in the range of, for example, 80°C to 350°C to perform a dehydrogenation process to produce a coarsely pulverized powder.
[0034] The average particle size of the coarsely pulverized powder is, for example, 10 μm or more and 500 μm or less. The average particle size (d50) in this disclosure can be measured by an airflow dispersion type laser diffraction method (based on JIS Z 8825: 2013 revised edition). That is, in this specification, the average particle size means the particle size (median diameter: d50) at which the cumulative particle size distribution (volume basis) from the small particle size side is 50%.
[0035] In the fine pulverization step, the coarsely pulverized powder is pulverized to obtain a fine powder having a median diameter d50 of, for example, 3.5 μm or less. The fine pulverization step may include a step of mixing an organic grinding aid with the coarsely pulverized powder. An example of the organic grinding aid is zinc stearate. The average particle size d50 of the finely pulverized powder is preferably 2.0 μm or more and 3.5 μm or less.
[0036] Next, a powder compact is produced from the finely pulverized powder by, for example, pressing in a magnetic field. In the case of pressing in a magnetic field, it is preferable to form the powder compact by pressing in an inert gas atmosphere or by wet pressing from the viewpoint of suppressing oxidation. In particular, in the case of wet pressing, the surfaces of the particles constituting the powder compact are covered with a dispersant such as an oil agent, suppressing contact with oxygen or water vapor in the air. Therefore, it is possible to prevent or suppress oxidation of the particles by the air before, during, or after the pressing process.
[0037] When wet pressing in a magnetic field is performed, a slurry is prepared by mixing a finely pulverized powder with a dispersion medium, and the slurry is supplied to a cavity in a mold of a wet pressing apparatus and press-molded in a magnetic field. The dispersion medium is a liquid in which a slurry can be obtained by dispersing an alloy powder therein. A preferred dispersion medium used in the present disclosure can be mineral oil or synthetic oil. Although the type of mineral oil or synthetic oil is not specified, if the kinetic viscosity at room temperature exceeds 10 cSt, the increase in viscosity may strengthen the bonding force between the alloy powders, which may adversely affect the orientation of the alloy powder during wet pressing in a magnetic field. For this reason, the kinetic viscosity of the mineral oil or synthetic oil at room temperature is preferably 10 cSt or less. Furthermore, if the fractional point of the mineral oil or synthetic oil exceeds 400°C, it becomes difficult to remove oil after obtaining a compact, and the amount of residual carbon in the sintered body may increase, resulting in a decrease in magnetic properties. Therefore, the fractional point of the mineral oil or synthetic oil is preferably 400°C or less. Vegetable oil may also be used as the dispersion medium. Vegetable oil refers to oil extracted from plants, and the type of plant is not limited to a specific plant.
[0038] The obtained alloy powder is mixed with a dispersion medium to obtain a slurry. The mixing ratio of the alloy powder and the dispersion medium is not particularly limited, but the concentration of the alloy powder in the slurry is preferably 70% or more (i.e., 70% by mass or more) in terms of mass ratio. 3 This is because, at a flow rate of 1000 / sec, the alloy powder can be efficiently supplied into the cavity and excellent magnetic properties can be obtained. The concentration of the alloy powder in the slurry is preferably 90% or less by mass ratio. The method of mixing the alloy powder and the dispersion medium is not particularly limited. The alloy powder and the dispersion medium may be prepared separately, and then the alloy powder and the dispersion medium may be weighed and mixed in a predetermined amount. In addition, when obtaining alloy powder by dry-pulverizing the coarsely pulverized powder with a jet mill or the like, a container containing the dispersion medium may be placed at the alloy powder outlet of the pulverizing device such as a jet mill, and the alloy powder obtained by pulverization may be directly collected in the dispersion medium in the container to obtain a slurry. In this case, it is preferable that the atmosphere inside the container is also made of nitrogen gas and / or argon gas, and the obtained alloy powder is directly collected in the dispersion medium without being exposed to the air to obtain a slurry. Furthermore, it is also possible to wet-pulverize the coarsely pulverized powder in the dispersion medium using a vibration mill, ball mill, attritor, or the like to obtain a slurry consisting of the alloy powder and the dispersion medium.
[0039] The slurry thus obtained can be molded in a known wet press to obtain a molded body having a desired size and shape. The molded body is sintered to obtain a sintered body. The powder molded body may also be molded in a dry press.
[0040] Next, the powder compact is sintered to obtain an RTB based sintered magnet material. The powder compact is preferably sintered at a pressure of 0.13 Pa (10 -3 Torr) or less, preferably 0.07 Pa (5.0 x 10 -4 The sintering is carried out under a pressure of 1000 to 1150 Torr or less at a temperature in the range of 1000° C. to 1150° C. In order to prevent oxidation due to sintering, the residual gas in the atmosphere may be replaced with an inert gas such as helium or argon.
[0041] <Step (S2) of Preparing Diffusion Source Powder> In the RA alloy, which is a diffusion source, R is a rare earth element including at least one selected from the group consisting of Nd, Pr, and Ce, and A is an element including at least one selected from the group consisting of Cu, Fe, Co, Ni, Al, Ag, Zn, Si, Sn, Ga, B, and C, and must include Cu.
[0042] It is preferable that the composition ratio of R is 60% by mass or more and 94.5% by mass or less of the entire RA alloy, the composition ratio of Cu is 5% by mass or more and 20% by mass or less of the entire RA alloy, and the composition ratio of A other than Cu is 0% by mass or more and 20% by mass or less of the entire RA alloy.
[0043] The diffusion source can be prepared by a method for producing a raw material alloy that is employed in a general manufacturing method typified by Nd-Fe-B sintered magnets, such as a die casting method, a strip casting method, a single roll super-quenching method (melt spinning method), or an atomizing method. The diffusion source may also be an alloy obtained by the above method, which has been pulverized by a known pulverizing means such as a pin mill. In order to improve the pulverizability of the alloy obtained by the above method, the alloy may be heat-treated in a hydrogen atmosphere at 700°C or less to incorporate hydrogen, and then pulverized.
[0044] <Step (S3) of diffusing from the diffusion source into the RTB sintered magnet material> By performing heat treatment at a temperature of 700°C to 1100°C in a vacuum or inert gas atmosphere, the elements contained in the diffusion source are diffused from the surface of the sintered body to the inside. If the heat treatment temperature for diffusion is less than 700°C, the diffusion is insufficient and a high H cJ On the other hand, if the temperature exceeds 1100℃, abnormal grain growth of the main phase occurs, and H cJ The heat treatment temperature for diffusion is preferably 800°C or higher and 1000°C or lower. cJThe heat treatment time is set to an appropriate value depending on the composition and dimensions of the magnet material and diffusion source, the heat treatment temperature, etc., and is preferably from 5 minutes to 30 hours, more preferably from 10 minutes to 25 hours, and even more preferably from 30 minutes to 20 hours. It is also preferable to prepare the diffusion source in an amount of from 1 mass% to 30 mass% of the weight of the magnet material. If the diffusion source is less than 1 mass% of the weight of the magnet material, H cJ On the other hand, if it exceeds 30 mass%, B r may decrease.
[0045] The heat treatment for diffusion can be performed using a known heat treatment method. For example, the surface of the magnet material can be covered with a powder layer of the diffusion source, and the first heat treatment can be performed. For example, the diffusion source can be coated on the surface of the sintered body material by a sputtering method, and then the first heat treatment can be performed. For example, a slurry in which the diffusion source is dispersed in a dispersion medium can be applied to the surface of the magnet material, and the dispersion medium can be evaporated to bring the diffusion source into contact with the sintered body material. Examples of the dispersion medium include alcohol (ethanol, etc.), NMP (N-methylpyrrolidone), aldehydes, and ketones. In addition, the magnet material that has been subjected to the first heat treatment can be subjected to known mechanical processing such as cutting or machining.
[0046] Next, the multi-stage heat treatment process in this embodiment will be described with reference to FIG.
[0047] <First heat treatment step (S10)> In the first heat treatment step (S10), the RTB based sintered magnet material after the element diffusion is heat treated at a first temperature (T1) of 400°C to 430°C for 30 to 300 minutes (first heat treatment time t1). This heat treatment is preferably performed in a heat treatment furnace (heat treatment chamber) filled with a vacuum or inert gas atmosphere. The first temperature (T1) is preferably 410°C to 430°C. Furthermore, a preheating step may be performed before the first heat treatment step, in which the temperature of the heat treatment furnace is kept between 300°C to 380°C for 30 to 200 minutes. This is because the uniformity of the temperature distribution in the heat treatment furnace is improved. The preheating step is preferable, since it contributes to reducing the variation in magnetic properties between magnets, particularly when multiple RTB based sintered magnet materials are heat treated in the heat treatment furnace.
[0048] The first heat treatment step (S10) creates R6T at the grain boundaries. 13 It is believed that the formation of RTA phases such as Ga phases proceeds.
[0049] <Cooling step (S20)> Next, a step (S20) is performed in which the temperature of the RTB based sintered magnet material is cooled to a cooling temperature of 300°C or less. The cooling rate is, for example, 10 to 100°C / min. The cooling step may be performed in the heat treatment furnace in which the first heat treatment step (S10) was performed, or the RTB based sintered magnet material may be moved from the heat treatment furnace (heat treatment chamber) to a cooling chamber filled with an inert gas and cooled. In a preferred embodiment, the cooling temperature (T0) is 100°C or less (for example, about room temperature, 20 to 30°C). The cooling time t0 is, for example, 30 minutes or more. In this case, the cooling time t0 refers to the time during which the temperature of the RTB based sintered magnet material is in a state of 300°C or less.
[0050] From the results of the experimental example described later, it is believed that the state of the grain boundary phase after the subsequent second heat treatment step (S30) changes depending on whether or not there is a cooling step (S20). Although the specific mechanism is unknown, it is believed that the R6T 13After generating RTA phases such as Ga phases at the grain boundaries, a cooling step (S20) is performed, so that H cJ While achieving an increase in r It is possible to suppress the decrease in the
[0051] <Second heat treatment step (S30)> In the second heat treatment step (S30), the RTB based sintered magnet material is heat treated at a second temperature (T2) of 430°C or more and 530°C or less for 30 minutes or more and 200 minutes or less (t2). This heat treatment is preferably performed in the heat treatment furnace in which the first heat treatment step (S10) was performed, but may be performed in another heat treatment furnace. The second temperature (T2) is preferably 440°C or more and 475°C or less. The rate of temperature rise from the cooling temperature (T0) to the second temperature (T2) is, for example, 0.5°C / min or more and 30°C / min or less. The second temperature is 30°C or more and 130°C or less higher than the first temperature. Preferably, the second temperature is 30°C or more and 100°C or less higher than the first temperature. Higher H cJ Because you can get it.
[0052] As described above, the first heat treatment step (S10) 13 It is believed that the formation of RTA phases such as Ga phases will proceed, but by performing a further cooling step (S20) and a second heat treatment step (S30) at a second temperature (T2) higher than the first temperature (T1), the formation of B r While suppressing the decline of H cJ This has the effect of improving the
[0053] The RTB based sintered magnet obtained by the multi-stage heat treatment in this embodiment is B r While suppressing the decline of cJ By heat treatment, R6T can be obtained at the grain boundaries. 13 The formation of RTA phases such as Ga phases progresses. In other words, by performing a relatively low-temperature heat treatment and a relatively high-temperature heat treatment with a cooling process in between, the grain boundary phase is controlled and the B r While suppressing the decline of H cJIt is also preferable to carry out the above-mentioned pre-heating step before the second heat treatment step. EXAMPLES
[0054] The present disclosure will be described in more detail with reference to examples, but the present disclosure is not limited thereto.
[0055] Experimental Example 1 First, the raw materials of each element were weighed so that the RTB sintered magnet would have the composition shown in Table 1, and alloys were produced by strip casting. The resulting alloys were coarsely pulverized by hydrogen pulverization to obtain coarsely pulverized powder. Next, zinc stearate was added as a lubricant to the resulting coarsely pulverized powder in an amount of 0.04 mass% relative to 100 mass% of the coarsely pulverized powder, and after mixing, the mixture was dry-pulverized in a nitrogen stream using an airflow pulverizer (jet mill device). The average particle size d50 of the finely pulverized powder was 2.7 μm.
[0056] [Table 1]
[0057] Next, the slurry of the finely pulverized powder was pressed in a magnetic field using a press molding device to produce a powder compact. As the press molding device, a so-called perpendicular magnetic field molding device (horizontal magnetic field molding device) in which the magnetic field application direction and the pressure direction are perpendicular to each other was used. The molding conditions were as shown in Table 2.
[0058] [Table 2]
[0059] The obtained powder compact was sintered in a vacuum at 1060°C for 4 hours to obtain an RTB-based sintered magnet. The density of the obtained RTB-based sintered magnet material was 7.5 Mg / m 3 That was all.
[0060] The results of the components of the obtained RTB based sintered magnet material are shown in the above-mentioned Table 1. Note that for each component in Table 1, Nd, Pr, Dy, B, Co, Al, Cu, Ga, and Zr were analyzed by ICP (inductively coupled plasma) atomic emission spectrometry, O was analyzed by gas fusion-infrared absorption spectrometry, N was analyzed by gas fusion-thermal conduction spectrometry, and C was analyzed by combustion-infrared absorption spectrometry.
[0061] A diffusion source of RA alloy was prepared. Specifically, a diffusion source powder of Pr-Cu alloy (Pr: 90 mass% + Cu: 10 mass%) and a Pr-Tb-Ga-Cu alloy (Pr: 77 mass% + Tb: 13 mass% + Ga: 5 mass% + Cu: 5 mass%) were prepared. The particle size of the diffusion source powder was under 110μm. The RTB sintered magnet material after sintering was cut and the entire surface was ground to prepare a cubic sample of 7.2mm x 7.2mm x 7.2mm. The prepared diffusion source powder of Pr-Cu alloy (Pr: 90 mass% + Cu: 10 mass%) or Pr-Tb-Ga-Cu alloy (Pr: 77 mass% + Tb: 13 mass% + Ga: 5 mass% + Cu: 5 mass%) was applied to the surface of the sample, and a diffusion process was performed at 900℃ for 600 minutes to obtain an RTB sintered magnet material.
[0062] The RTB sintered magnet material after diffusion was heat-treated under various conditions, then ground using a surface grinder to produce cubic samples measuring 7.0 mm x 7.0 mm x 7.0 mm. The residual magnetic flux density B r and coercive force H cJ The preparation conditions for each sample, including the heat treatment conditions, and the resulting magnetic properties are shown in Table 3. The coating amount in the table is the weight of the diffusion source powder coated on the surface of the RTB based sintered magnet, expressed as a mass percentage relative to 100 mass% of the RTB based sintered magnet material.
[0063] [Table 3]
[0064] In Table 3, 1 hr means 60 minutes, and 2 hr means 120 minutes. Nos. 1 to 3 in Table 3 show the relationship between the magnetic properties and the presence or absence of the first heat treatment step and the cooling step. No. 2 does not undergo the cooling step, so cooling is not performed after the first heat treatment, and the temperature is raised at 10°C / min from the first heat treatment temperature T1 to the treatment temperature T2 of the second heat treatment. Note that all of the examples of the present invention that undergo the cooling step are cooled to room temperature (25°C) after the first heat treatment. As shown in Table 3, No. 3 (example) has a B value lower than Nos. 1 and 2. r While suppressing the decline of cJ No. 4 is a comparative example in which the temperatures T1 (first temperature) and T2 (second temperature) in the conditions of No. 3 are interchanged. In this comparative example, No. 3 (Example) also has a smaller B than No. 4. r While suppressing the decline of cJ Similarly, when comparing Nos. 5 to 7, 8 to 10, 11 and 12, and 13 to 15, which are the same diffusion source and have the same second heat treatment temperature and time, the examples of the present invention are all superior to the comparative examples in terms of B r While suppressing the decline of cJ Thus, an RTB-based sintered magnet having the above properties has been obtained.
[0065] Experimental Example 2 In Experimental Example 2, the same RTB based sintered magnet material as "Material B" in Experimental Example 1 was subjected to the following treatment.
[0066] First, a diffusion source of RA alloy was prepared. Specifically, a diffusion source powder of Pr-Cu alloy (Pr: 90 mass% + Cu: 10 mass%) was prepared. The particle size of the diffusion source powder was under 110μm. The sintered RTB sintered magnet material (material B) was cut and the entire surface was ground to produce a cubic sample of 7.2mm x 7.2mm x 7.2mm. The prepared diffusion source powder of Pr-Cu alloy (Pr: 90 mass% + Cu: 10 mass%) was then applied to the surface of the sample, and a diffusion process was performed at 900℃ for 600 minutes to obtain an RTB sintered magnet material.
[0067] The RTB sintered magnet material after diffusion was heat-treated under various conditions, then ground using a surface grinder to produce cubic samples measuring 7.0 mm x 7.0 mm x 7.0 mm. The residual magnetic flux density B r and coercive force H cJ The preparation conditions for each sample, including the heat treatment conditions, and the obtained magnetic properties are shown in Table 4. The coating amount in the table is the weight of the diffusion source powder coated on the surface of the RTB based sintered magnet, expressed as a mass percentage relative to 100 mass% of the RTB based sintered magnet material.
[0068] [Table 4]
[0069] Nos. 16 to 19 in Table 4 show the influence on the magnetic properties of the presence or absence of the second heat treatment step and the duration of the second heat treatment step when the first heat treatment step is not performed. Nos. 20 to 24 show the influence on the magnetic properties of the presence or absence of the second heat treatment step and the duration of the second heat treatment step when the preheating and the first heat treatment steps are performed. No. 21 was produced under the same conditions as No. 9 in Table 3.
[0070] As shown in Table 4, No. 21 (Example) and No. 22 (Example) have a higher B than Nos. 16 to 20 (Comparative Examples). r While suppressing the decline of cJIn the case of No. 24 (Example), the RTB sintered magnet has a higher B than in the case of No. 23 (Comparative Example). r While suppressing the decline of cJ Thus, an RTB-based sintered magnet having the above properties has been obtained.
[0071] As described above, the present disclosure includes the methods for producing RTB based sintered magnets described in the following items. [Item 1] preparing an RTB sintered magnet material (R is a rare earth element including at least one selected from the group consisting of Nd, Pr, and Ce, T is an element including at least one selected from the group consisting of Fe, Co, Al, Mn, and Si, the mass ratio of T being 90% or more being Fe, and B being boron); RA alloy (R is at least one element selected from the group consisting of Nd, Pr and Ce) A is a rare earth element including at least one selected from the group consisting of Cu, Fe, Co, Ni, Al, Ag, Zn, Si, Sn, Ga, B and C, and always includes Cu; diffusing an element contained in the diffusion source from the diffusion source into the RTB based sintered magnet material; a first heat treatment step of heat treating the RTB based sintered magnet material at a first temperature of 400° C. or more and 430° C. or less for a period of 30 minutes or more and 300 minutes or less; a step of cooling the RTB based sintered magnet material to a temperature of 300° C. or less after the first heat treatment step; a second heat treatment step of heat treating the RTB based sintered magnet material at a second temperature of 430° C. or more and 530° C. or less for 30 minutes or more and 200 minutes or less after the cooling step; Including, The second temperature is 30° C. or more and 130° C. or less higher than the first temperature; Manufacturing method for RTB sintered magnets. [Item 2] The first temperature is equal to or higher than 410° C. and equal to or lower than 430° C. 2. The method for producing an RTB based sintered magnet according to item 1, wherein the second temperature is 440° C. or higher and 475° C. or lower. [Item 3] diffusing an element contained in the diffusion source from the diffusion source into the RTB based sintered magnet material; a step of adhering the powder of the diffusion source to a surface of the RTB based sintered magnet material; A step of performing a heat treatment at a temperature of 700°C or more and 1100°C or less in a vacuum or inert gas atmosphere; 3. A method for producing an RTB based sintered magnet according to item 1 or 2, comprising: [Industrial Applicability]
[0072] The method for producing an RTB based sintered magnet according to the present disclosure can be used to produce permanent magnets for a wide variety of applications, such as voice coil motors (VCMs) for hard disk drives, motors for electric vehicles (EVs, HVs, PHVs), motors for industrial equipment, and other motors, as well as home appliances. [Explanation of symbols]
[0073] 12 Main phase 14 Grain boundary phase 14a Two-grain grain boundary phase 14b Grain boundary triple point
Claims
1. preparing an R-T-B based sintered magnet material (R is a rare earth element including at least one selected from the group consisting of Nd, Pr, and Ce, T is an element including at least one selected from the group consisting of Fe, Co, Al, Mn, and Si, the mass ratio of T being 90% or more of Fe, and B being boron); A step of preparing a diffusion source of an R-A alloy (R is a rare earth element including at least one selected from the group consisting of Nd, Pr, and Ce, and A is an element including at least one selected from the group consisting of Cu, Fe, Co, Ni, Al, Ag, Zn, Si, Sn, Ga, B, and C, and always including Cu); a step of diffusing an element contained in the diffusion source from the diffusion source into the R-T-B based sintered magnet material; a first heat treatment step of heat treating the sintered R-T-B based magnet material at a first temperature of 400° C. or more and 430° C. or less for 30 minutes or more and 300 minutes or less; a step of cooling the sintered R-T-B based magnet material to a temperature of 300° C. or lower after the first heat treatment step; a second heat treatment step of heat treating the sintered R-T-B based magnet material at a second temperature of 430° C. or more and 530° C. or less for 30 minutes or more and 200 minutes or less after the cooling step; Including, The second temperature is higher than the first temperature by 30° C. or more and 130° C. or less. A method for producing an RTB based sintered magnet.
2. The first temperature is equal to or higher than 410° C. and equal to or lower than 430° C.
2. The method for producing a sintered RTB based magnet according to claim 1, wherein the second temperature is 440° C. or higher and 475° C. or lower.
3. The step of diffusing the element contained in the diffusion source from the diffusion source into the sintered R-T-B based magnet material includes: a step of adhering the diffusion source powder to a surface of the sintered R-T-B magnet material; A step of performing a heat treatment at a temperature of 700° C. or more and 1100° C. or less in a vacuum or inert gas atmosphere; 3. The method for producing a sintered R-T-B based magnet according to claim 1, comprising:
Citation Information
Patent Citations
Alloy for r-t-b-based rare earth sintered magnet, process for producing alloy for r-t-b-based rare earth sintered magnet, alloy material for r-t-b-based rare earth sintered magnet, r-t-b-based rare earth sintered magnet, process for producing r-t-b-based rare earth sintered magnet, and motor
WO2013008756A1